Application Of Thematic Pop Up Book Media In Improving Language Ability Of Children Aged 4–5 Years - Feorintina Gloria Ester Atimeta; Puput Kartiqha Airtur; Yustina Indriyani Dhelo; Yufita Seubelan; Yesaya Binoni Bayang; Fredericksen Victoranto Amseke (Jurnal E-MAS (Edukasi dan Pembelajaran Anak Usia Dini), 2026)
Background: Language ability is a fundamental aspect of early childhood development as it supports communication, comprehension, and expression skills. However, limited empirical evidence has examined the use of thematic Pop Up Book media in authentic classroom settings using an ex post facto design. Objective: This study aimed to examine the effect of thematic Pop Up Book media on the language ability of children aged 4–5 years at PAUD Nekafhonis. Method: A quantitative approach with an ex post facto design was employed involving 17 children selected through total sampling. Data were collected using thematic Pop Up Book media and language ability scales and analyzed using descriptive statistics and simple linear regression with SPSS 25.0. Results: The findings revealed that thematic Pop Up Book media had a positive and significant effect on children’s language ability, with an R Square value of 0.242, indicating a contribution of 24.2%. The significance value was 0.045 (p < 0.05), confirming the hypothesis. Novelty: This study provides empirical evidence of the effectiveness of thematic Pop Up Book media in improving early childhood language ability within a real classroom context using an ex post facto design. Conclusion: Consistent and structured implementation of thematic Pop Up Book media can significantly enhance children’s language development and support active learning in early childhood education.